Esterifikasi Asam Lemak Dengan Katalis Enzim Pada Sintesis Emulsifier - Mulya, Dynna Ardilla Putri; Zahrina, Ida; Helwani, Zuchra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Monoglycerides, the glycerol monoesters of fatty acids, are molecules consisting of a hydrophilic head and a hydrophobic tail with surfactant and emulsifying properties that help hydrophilic-lipophilic substances mix all together. Therefore, they can be used in food, detergent, plasticizer, cosmetic and pharmaceutical formulations. Monoglycerides (MG) and diglycerides (DG) are a group of synthetic emulsifiers obtained from the process of esterification of fatty acids with glycerol using an organic catalyst, enzyme, and solid catalyst. . In this journal, a green technology catalyst was used in the form of enzyme catalyst. Enzymes are proteins that act as biological catalysts (biocatalysts). Catalysts accelerate chemical reactions. The molecules upon which enzymes may act were called substrate and the enzyme converts the substrate into different molecules known as products. Lipase enzymes were used for biotechnological applications in the dairy, oil, surfactant, and pharmaceutical industries. The production of biotechnology products using the enzyme lipase is the usual choice in line with the rapid progress of development. Keywords: enzyme catalysts, esterification, lipase enzyme, monoglycerides